Overtourism: the accident and the disaster in Capitólio-MG - Vieira, Giovana Araújo; Gonçalves, Julia Pereira; Oliveira, Rodrigo Ribeiro de; Lima, Rosineide Maria de; Alves, Thiago Monteiro (Brazilian Journal of Production Engineering, 2022)
Overtourism is understood as any activity characterized by the overcrowding of tourist destinations, where tourist receptivity is not controlled or even poorly managed. Relating the overtourism with the cargo capacity in Capitólio-MG, it can be said that there is a certain lack of control of tourist activities, disorderly services in the activities of vessels, in addition to the fact that only one employee for a high number of tourists, causing an uncontrolled overload. of boats and equipment. The collapse of a large rock block, which occurred in January 2022, was a disaster that left 10 dead and 27 people injured, and due to the large flow of tourists in the region, some safety procedures were not carried out in accordance with Civil Defense guidelines, who advised not to use the space during the same weekend that the accident took place. For this, a qualitative, exploratory and descriptive research was carried out with a basic purpose, whose data collection procedure took place through bibliographic and documentary research in order to suggest hypotheses to avoid disasters such as the one in the Furnas Canyons in the future. The accident does not qualify as a fatality, however, the planning failed to analyze and qualify the risk agents who were exposed to tourists.
Keywords: Predatory tourism; Overtourism; Safety Rules; Natural Disasters; Accidents